2012
DOI: 10.1371/journal.pone.0037210
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Disturbances Associated with Systemic Lupus Erythematosus

Abstract: The metabolic disturbances that underlie systemic lupus erythematosus are currently unknown. A metabolomic study was executed, comparing the sera of 20 SLE patients against that of healthy controls, using LC/MS and GC/MS platforms. Validation of key differences was performed using an independent cohort of 38 SLE patients and orthogonal assays. SLE sera showed evidence of profoundly dampened glycolysis, Krebs cycle, fatty acid β oxidation and amino acid metabolism, alluding to reduced energy biogenesis from all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
169
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(197 citation statements)
references
References 19 publications
18
169
0
2
Order By: Relevance
“…In contrast, a metabolomics study on SLE sera revealed reduced glycolysis, Krebs cycle, fatty acid β oxidation, and aa metabolism in these patients compared to healthy controls. This dysregulation associates with dampened energy generation, high oxidative stress, inflammation, altered lipid profiles, and a prothrombotic state [69]. Furthermore, serum levels of total LDH, LDH1, and LDH2 were significantly higher in patients with diffuse proliferative lupus nephritis and showed good correlations with the activity index and the total pathologic score of the renal pathologic scoring system, and with the glomerular hypercellularity.…”
Section: Metabolic Dysregulation In Ra and Other Autoimmune Conditionsmentioning
confidence: 94%
“…In contrast, a metabolomics study on SLE sera revealed reduced glycolysis, Krebs cycle, fatty acid β oxidation, and aa metabolism in these patients compared to healthy controls. This dysregulation associates with dampened energy generation, high oxidative stress, inflammation, altered lipid profiles, and a prothrombotic state [69]. Furthermore, serum levels of total LDH, LDH1, and LDH2 were significantly higher in patients with diffuse proliferative lupus nephritis and showed good correlations with the activity index and the total pathologic score of the renal pathologic scoring system, and with the glomerular hypercellularity.…”
Section: Metabolic Dysregulation In Ra and Other Autoimmune Conditionsmentioning
confidence: 94%
“…LC/MS and GC/MS platforms were used to compare metabolite profiling in the serum between SLE patients and healthy controls. The SLE patients presented elevated lipid peroxidation products, MDA, gamma-glutamyl peptides, GGT, leukotriene B4 and 5-HETE, which indicated lipid peroxidation and oxidative damage (Wu et al, 2012). Using NMR spectrums accompanied with the PCA and OPLS-DA models, the SLE serum samples were characterized by decreased concentrations of valine, tyrosine, phenylalanine, lysine, isoleucine, histidine, glutamine, alanine, citrate, creatinine, creatine, pyruvate, high-density lipoprotein, cholesterol, glycerol, formate and increased concentrations of N-acetyl glycoprotein, very low-density lipoprotein and low-density lipoprotein (Ouyang et al, 2011).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 96%
“…SLE lymphocytes have hypomethylated DNA and increased oxidative stress due to the depletion of GSH [17,27,49]. This may be due to the accumulation of SAH from blockage in the SAM pathway that prevents recycling of SAH and homocysteine to methionine or cystathionine.…”
Section: Dna Modificationsmentioning
confidence: 99%